Lumba-Lumba Hidung Botol Laut Jawa Adalah Tursiops aduncus Berdasar Sekuen Gen NADH Dehidrogenase Subunit 6 (VERIFICATION BOTTLENOSE DOLPHINS FROM JAVA SEA IS TURSIOPS ADUNCUS BASED ON GENE SEQUENCES OF NADH DEHYDROGENASE SUBUNIT 6) - Widayanti, Rini; Fibrianto, Yuda Heru; Wendo, Woro Danur (Jurnal Veteriner; Vol 15 No 1 (2014), 2014)
Bottlenose dolphins (Tursiops sp.) is one of the aquatic mammals widely spread in the marines ofIndonesia archipelago, especially the Java Sea. The taxonomy of the genus Tursiops is still  controversial.The purpose of this study was to examine the molecular basis of Tursiops sp of Java sea marine origin onthe basis of its NADH dehydrogenase gene subunit 6 (ND6) sequences. Samples of blood were collectedfrom five male bottle nose dolphins from captivity of PT. Wersut Seguni Indonesia. DNA was isolated,amplified by polymerase chain reaction (PCR), sequenced, and analyzed the data using the MEGA v. 5.1program. The results of PCR amplification was 868 base pairs (bp), DNA sequencing showed that 528nucleotides were ND6 gene, nucleotide at the position of 387 could be used to distinguish the bottle nosedolphins Java marine origin with T. aduncus.   Filogram using Neighbor joining method based on thenucleotide sequence of the gene ND6, showed that bottle nose dolphins Java marine origin belong to groupof T. aduncus.
Keywords: bottlenose dolphins, ND6 gene, nucleotide, Java Sea